Atom-economic catalytic amide synthesis from amines and carboxylic acids activated in situ with acetylenes - Thilo Krause (Nature Portfolio, 2016)
Amide formation is a ubiquitous reaction in organic chemistry, but suffers from the problem of generating large amounts of waste. Here, the authors report a catalytic amide synthesis by the ruthenium catalysed addition of carboxylic acids to acetylenes, followed by reaction with primary or secondary amines.